2017
DOI: 10.18632/oncotarget.21610
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide is cytoprotective to breast cancer spheroids vulnerable to estrogen-induced apoptosis

Abstract: Estrogen-induced apoptosis has become a successful treatment for postmenopausal metastatic, estrogen receptor-positive breast cancer. Nitric oxide involvement in the response to this endocrine treatment and its influence upon estrogen receptor-positive breast cancer progression is still unclear.Nitric oxide impact on the MCF7 breast cancer line, before and after estrogen-induced apoptosis, was investigated in 3D culture systems using unique live-cell imaging methodologies.Spheroids were established from MCF7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, studies have showed that NO may also play an important role in cancer related pathophysiology such as modifying the expression of oncogene and tumor suppressor gene, tumor angiogenesis and metastasis [1]. NO has different actions in various human cancers such as head and neck cancer, breast cancer, gastric cancer, lung cancer and gynecologic cancers [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have showed that NO may also play an important role in cancer related pathophysiology such as modifying the expression of oncogene and tumor suppressor gene, tumor angiogenesis and metastasis [1]. NO has different actions in various human cancers such as head and neck cancer, breast cancer, gastric cancer, lung cancer and gynecologic cancers [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Several decades of literature highly supports the involvement NO as a pleiotropic onco-regulatory gasotransmitter in several types of cancers including BC (Shafran et al, 2017;Yarlagadda, Hassani, Foote, & Markowitz, 2017). Recently, eNOS-induced NO production has been highly implicated in determining the aggressiveness of TNBC tumors (Cranford et al, 2017;Trimmer et al, 2011;).…”
mentioning
confidence: 96%
“…Moreover, NO can prevent tumour cells from metastasising and assists macrophage to kill tumour cells 55 . Furthermore, evidences showed that low levels (nanomolar) of NO promote tumour cell proliferation, angiogenesis and metastasis, while higher concentrations sensitivity of tumours to chemotherapy and overcome drug resistance 56 . Therefore combination of high concentrations NO donors and cancer therapy increases its efficiency 57 .…”
Section: Introductionmentioning
confidence: 99%